1998
DOI: 10.2136/sssaj1998.03615995006200050045x
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Detrital Organic Carbon in a Nutrient‐Impacted Everglades Marsh

Abstract: Phosphorus loading to the Everglades from nearby agricultural areas has become a major concern, and is considered to be a significant factor in the encroachment of cattail (Typha domingensis Pers.) and other rapidly growing vegetation into endemic sawgrass (Cladium jamaicense Crantz) marsh. The objectives of this research were to evaluate the variability in turnover of organic C in plant and soil detrital pools along a P enrichment gradient in an Everglades marsh and to identify substrate characteristics and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 0 publications
8
103
0
Order By: Relevance
“…Although direct carbon quality measures (e.g., C : N, lignin) are often used to explain rates of litter decomposition [11], they do not explain the differences in the denitrification rate constants here as well as the acid soluble carbohydrate fraction of the litter. The characteristically low litter C : N of the two floating aquatics (marsh pennywort and duckweed) did not correspond to consistently higher rate constants, only the bulrush litter exhibited significantly lower denitrification rate constants at high lignin and C : N ratios.…”
Section: Regulation Of Denitrification Activity By Carbon Quality Of mentioning
confidence: 98%
See 2 more Smart Citations
“…Although direct carbon quality measures (e.g., C : N, lignin) are often used to explain rates of litter decomposition [11], they do not explain the differences in the denitrification rate constants here as well as the acid soluble carbohydrate fraction of the litter. The characteristically low litter C : N of the two floating aquatics (marsh pennywort and duckweed) did not correspond to consistently higher rate constants, only the bulrush litter exhibited significantly lower denitrification rate constants at high lignin and C : N ratios.…”
Section: Regulation Of Denitrification Activity By Carbon Quality Of mentioning
confidence: 98%
“…It is possible that this may have affected the carbon supplied for subsequent experimental conditions, since these materials appear to be very rapidly assimilated by attached bacteria in wetlands [5]. Other authors have shown senescent wetland plants and litter become rapidly depleted of their soluble carbohydrates and higher molecular weight compounds such as lignins with low hydrolysis rates [19] are selectively concentrated in the remaining litter [11]. For this reason, carbon supplied by the developing peat and litter arriving from the prior year's plant productivity may contribute less to denitrification activity than the rapidly hydrolyzed carbohydrates in fresh and senescent litter.…”
Section: Regulation Of Denitrification Activity By Carbon Quality Of mentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in "nutrient leakage". Organic matter turnover rates and nutrient leaching losses are often increased in eutrophic sites (Wedin and Tilman 1996;Debusk and Reddy 1998). In NW Europe, eutrophic sites are most often invaded by F. japonica, S. gigantea, I. glandulifera and H. mantegazzianum.…”
Section: Decreased Pools Of Nutrients In the Topsoil In Nutrient-richmentioning
confidence: 99%
“…Generally, an abundant oxygen supply promotes rapid soil organic matter decomposition, whereas a deficiency in oxygen results in a substantially lower decomposition rate (DeBusk et al 2001;Shaffer and Ma 2001), with the carbon mineralization rates in aerobic conditions being as much as three times faster than under anaerobic conditions (DeBusk and Reddy 1998). Thus, the presence of saturated soil conditions that occur in rice-based cropping systems can affect the release rates and patterns of carbon gas emissions from the soil.…”
Section: Introductionmentioning
confidence: 99%